Pengaruh Literasi Keuangan Dan Disiplin Kerja Terhadap Kinerja Pekerja Industri Meubel Di Desa Touliang Oki - Tivany Maerah; Consuslasia Korompis; Joubert M. Dame (Jurusan Pendidikan Ekonomi Fakultas Ekonomi dan Bisnis UNIMA, 2020)
This study aims to determine the extent of the influence of financial literacy and work discipline on the performance of furniture industry workers in the village of Touliang Oki The method used in this study uses a type of quantitative research survey method The population in this study was 51 and the research sample was 45 Based on data analysis The results showed that financial literacy has a positive or significant effect on employee performance Thus the first hypothesis is accepted The results showed that work discipline has a positive or significant effect on employee performance Thus the second hypothesis is accepted The results showed that Financial Literacy and Work Discipline had a positive or significant effect together on employee performance Thus the third hypothesis is accepted < p> nbsp;< p>